Real-time feedback system for monitoring and facilitating discussions - Constable, Martin (Springer Science+ Business Media New York, 2014)
In this chapter, we present a system that provides real-time feedback about an ongoing discussion. Various speech statistics, such as speaking length, speaker turns and speaking turn duration, are computed and displayed in real time. In social monitoring, such statistics have been used to interpret and deduce talking mannerisms of people and gain insights on human social characteristics and behaviour. However, such analysis is usually conducted in an offline fashion, after the discussion has ended. In contrast, our system analyses the speakers and provides feedback to the speakers in real time during the discussion, which is a novel approach with plenty of potential applications. The proposed system consists of portable, easy to use equipment for recording the conversations. A user-friendly graphical user interface displays statistics about the ongoing discussion. Customized individual feedback to participants during conversation can be provided. Such close-loop design may help individuals to contribute effectively in the group discussion, potentially leading to more productive and perhaps shorter meetings. Here we present preliminary results on two-people face to face discussion. In the longer term, our system may prove to be useful, e.g. for coaching purposes and for facilitating business meetings.